The Effect of Production Inputs on Productivity and Production Risk of Cloves in East Java Province - Izumi Risma Ayuka; Anna Fariyanti; Etriya Etriya (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: The demand for cloves, both domestically and internationally, continues to rise. However, clove productivity in East Java Province has shown fluctuations and a declining trend during the 2015 - 2022 period. This decline is influenced by various factors, including suboptimal farming input allocation, pest attacks, unpredictable weather conditions, and the cyclical nature of clove production.Purpose: This paper examines the influence of production inputs on clove productivity and production risks in East Java Province. Design/methodology/approach: This paper utilized secondary data from the 2014 Household Agricultural Survey, incorporating a sample of 937 clove farming households in East Java Province. The Just and Pope Model was utilized to evaluate the influence of production inputs on clove productivity and production risks.Findings/Results: The analysis demonstrates that clove production risks in East Java are high, as indicated by a coefficient of variation (CV) greater than 0.5. Production inputs that increase clove productivity include family labor, external labor, organic fertilizers, pesticides, and plant population. However, the application of TSP fertilizers decreases clove productivity. Furthermore, the application of ZA fertilizers increases production risks, while family labor decreases production risks.Conclusion: The findings emphasize the critical importance of managing production inputs to improve clove productivity and reduce associated risks. Key recommendations include implementing training programs to enhance farmers’ knowledge, providing subsidies to encourage efficient input use, and adopting effective pest control strategies. These interventions are essential for promoting the sustainability and resilience of clove farming in East Java. This study offers actionable insights for policymakers and stakeholders, supporting efforts to stabilize productivity and mitigate production risks.Originality/value: This paper adds to the understanding of production inputs influencing clove farming, particularly the input-related risks and productivity in East Java Province, providing insights for better farm management practices. Keywords: cloves, productivity, production risk, production input, East Java